1985
DOI: 10.1002/cjce.5450630412
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production by the catalytic steam reforming of methanol: Part 2: Kinetics of methanol decomposition using girdler G66B catalyst

Abstract: The rate of catalytic decomposition of methanol in the presence of steam has been studied using a commercial Girdler G66B CuO-ZnO low temperature shift catalyst from IS0 to 250°C at atmospheric pressure. The mole ratio of steam to methanol was varied from 0 to 1.5, and the feed rates covered the range from 300 to 1400 kg s/mol. The data were successfully correlated using a simple reaction network involving CH30H, HzO, CO and Hz. A conventional reversible reaction rate equation was used which included a resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
50
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(56 citation statements)
references
References 6 publications
5
50
0
1
Order By: Relevance
“…Structural investigations of the copper phase under reduction conditions based on XRD have been reported by Himelfarb et al (17) and Vong et al (18). Himelfarb et al and Porta et al ( 19) described an intermediary Cu 2 O phase, whereas this phase was not observed by Vong et al However, the detection of Cu 2 O is based on ex situ investigations which may not represent the "real" state of the Cu phase under reduction conditions. Als-Nielsen et.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Structural investigations of the copper phase under reduction conditions based on XRD have been reported by Himelfarb et al (17) and Vong et al (18). Himelfarb et al and Porta et al ( 19) described an intermediary Cu 2 O phase, whereas this phase was not observed by Vong et al However, the detection of Cu 2 O is based on ex situ investigations which may not represent the "real" state of the Cu phase under reduction conditions. Als-Nielsen et.…”
Section: Introductionmentioning
confidence: 97%
“…Cu/ZnO catalysts can be used to produce hydrogen by steam reforming of methanol with high selectivity and activity (1,2). Thus, methanol often is considered as an alternative "automotive" fuel and could serve as a potential hydrogen source for fuel cell applications (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, copper-based catalysts have received considerable attention for production of H 2 by SRM [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Recent papers have discussed the POM reaction [22][23][24], as well as the combined process for production of H 2 [25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Cu-based catalysts have been the most extensively studied SRM catalysts, and have been shown to be active as binary or ternary systems, in the presence of ZnO and Al 2 O 3 [5][6][7][8], and/or zirconia [9][10][11][12][13], ceria [14], and manganese oxide [15]. However, instability of this catalyst under fuel processing conditions at elevated temperature has been a recurring problem.…”
Section: Introductionmentioning
confidence: 99%